2022
DOI: 10.3390/agronomy12051109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humic Acids on Soybean Seedling Growth under Polyethylene-Glycol-6000-Induced Drought Stress

Abstract: Humic substances (HS) are the most important natural biostimulant of plants. However, the relationship between their structure and biological activity in plants is still not well recognized. The objective of this paper was to assess the influence of molecular fractions of humic acids (HA) (HA < 30 kDa and HA > 30 kDa) on reducing negative effects of drought stress in soybean (Glycine max (L.) Merr.) seedlings of Progres and Nawiko cultivars. Drought stress was induced in laboratory conditions by the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…These biostimulants substances can also promote the plant water status by increasing the relative water content and water potential, as well as increase N content leading to higher biomass accumulation in S. officinarum and C. melo plants under drought conditions ( Aguiar et al., 2016 ; Kıran et al., 2019 ). Matuszak-Slamani et al. (2022) also reported that HS (e.g., derived from vermicompost) increases several other morphological features in soybean, like fresh and plant dry matter of root and aboveground, and plant length under drought conditions.…”
Section: Mechanism Of Action Of Biostimulants For Mitigation Of Abiot...mentioning
confidence: 88%
“…These biostimulants substances can also promote the plant water status by increasing the relative water content and water potential, as well as increase N content leading to higher biomass accumulation in S. officinarum and C. melo plants under drought conditions ( Aguiar et al., 2016 ; Kıran et al., 2019 ). Matuszak-Slamani et al. (2022) also reported that HS (e.g., derived from vermicompost) increases several other morphological features in soybean, like fresh and plant dry matter of root and aboveground, and plant length under drought conditions.…”
Section: Mechanism Of Action Of Biostimulants For Mitigation Of Abiot...mentioning
confidence: 88%
“…However, the interaction between HA, FS and cultivars was found to be not significant for all the studied traits. In response to HA fertilized at the amount of 9 kg ha -1 , less (56) days to flowering was noted while more days to flowering (60) were seen in control plots. In case of FS, its application at the level of 8% had minimum days to flowering (56) which was not significantly different from 6% (58) in comparison to more days recorded (59) in control plots.…”
Section: Growth Attributes Of Soybeanmentioning
confidence: 94%
“…Improvement in seed protein was seen as result of higher HA and FS application compared to untreated units. Matuszak-Slamani et al [60] found that application of humic acid fractions caused an increase in chlorophyll content, which is an indicator of plant protein content. Additionally, a transcriptomic analysis by [61] revealed that humic acid could relieve the inhibitory effect of high nitrogen on soybean nodulation, which indirectly suggests a potential impact on the protein content of soybean.…”
Section: Oil and Protein Content Of Soybeanmentioning
confidence: 99%
“…Plants accommodate DS by using various mechanisms, including accumulation of osmolytes, hormones, and activation of the antioxidant defense system ( Hassan et al., 2020 ; Rasheed et al., 2022b ). Climate change and the consequent frequency of DS have adversely affected crop productivity globally ( Matuszak-Slamani et al., 2022 ). To increase crop productivity and counter the effects of DS, various strategies, including screening and breeding of tolerant cultivars, osmolytes, hormones, nutrient application, and microbes, can be used to increase crop production ( Arslan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%